Tracer Study of Bachelor of Elementary Education Graduates of the Davao Oriental State University – Cateel Extension Campus, Philippines - Apostol, Julie Mae A.; Susada, Bryan L. (Future Science / FSH-PH Publications, 2022)
Using a quantitative approach employing a descriptive survey research design, 150 Bachelor of Elementary Education (BEED) alumni of the Davao Oriental State University – Cateel Extension Campus (DORSU-CEC) from the classes of 2013-2021 were surveyed for to conduct this tracer study. Results revealed that most of graduates were females, single, employed regular or permanent basic education teachers within Davao Oriental under public or government organizations. Parents or relatives were very influential in their choice of program in college. Their main employer was the Department of Education (DepEd), and they occupied professional, technical or supervisory job level positions in their first and present employment. Further, graduates acquired their first job within 1 to 6 months after graduating in college, and earned a monthly income of almost ₱27,500 in their first and present employment. Moreover, graduates perceived that the curriculum offered to them in college was relevant in their first and present employment. They believed that communication skills and discipline that they learned in college are the most useful competency and core values on their employment. Additionally, the courses in the campus can be strengthened further if the library and laboratory are provided with more resources, equipment, and facilities that can aid the students in their studies, and if the campus offers more number of optional subjects.